Learning Innovation With The Theme Of Online-Based Learning Innovation - Achmad Nuryadi; Mulyono; Shandy Pieter Pelamonia; I Gede Dharma U; Ramadhany Hananto P; Riga Mardika (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2022)
To implement based on the results of the rapid survey analysis of learning from home during the COVID-19 prevention period, Ministry of Education and Culture April 2020, the obstacles faced by teachers in learning from home include the percentage of teachers' ability to operate digital devices of 67.11%, the availability of facilities and infrastructure owned by students. by 29.45%. Difficulty in understanding lessons is a complaint of the majority of students in almost all types of education units. There are difficulties in understanding related to subjects that are almost the same experienced by every level of our education, of course there needs to be a way how to need student assistance. In preparation for offline learning, SMPN 1 Tegalampel Bondowoso requires many references on how to innovate online learning. Therefore, it is necessary to hold counseling about Online Learning Innovation at SMPN 1 Tegalampel Bondowoso. The implementation of the Community Service Program activities by the Physical Education Lecturer Team at PGRI University Adi Buana Surabaya went smoothly. The teachers of SMPN 1 Tegalampel Bondowoso were very enthusiastic about participating in every scheduled activity. In order to prepare for offline learning, SMPN 1 Tegalampel Bondowoso needs many references on how to innovate online learning. Starting from knowledge of other innovations that can benefit all